2021
DOI: 10.1017/s1041610221001265
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory impairment in mild cognitive impairment with Lewy bodies and Alzheimer’s disease

Abstract: Objectives: Impaired olfaction may be a biomarker for early Lewy body disease, but its value in mild cognitive impairment with Lewy bodies (MCI-LB) is unknown. We compared olfaction in MCI-LB with MCI due to Alzheimer’s disease (MCI-AD) and healthy older adults. We hypothesized that olfactory function would be worse in probable MCI-LB than in both MCI-AD and healthy comparison subjects (HC). Design: Cross-sectional study assessing olfaction using Sniffin’ Sticks 16 (SS-16) in MCI-LB, MCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…DLB females had a thinner olfactory cortex than males. Olfactory alterations can discriminate DLB from AD 40–42 . Nonetheless, previous studies reported no sex differences in odor identification in DLB 40,42 .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…DLB females had a thinner olfactory cortex than males. Olfactory alterations can discriminate DLB from AD 40–42 . Nonetheless, previous studies reported no sex differences in odor identification in DLB 40,42 .…”
Section: Discussionmentioning
confidence: 82%
“…[40][41][42] Nonetheless, previous studies reported no sex differences in odor identification in DLB. 40,42 Investigating sex differences in olfactory identification and their brain correlates could help characterize the less investigated "olfactory bulb only" subtype of DLB. 43 We recently showed that the olfactory cortex is one of the regions that discriminates two DLB subtypes with widespread predominant cortical atrophy and predominant fronto-occipital atrophy.…”
Section: Discussionmentioning
confidence: 86%
“…Hyposmia: In one study, self‐reported loss of smell was common in MCI‐LB (44%) and MCI‐AD (19%) 33 . Two studies have measured olfactory function using standardized tests 20, 34 . Both studies found poorer olfactory function in MCI‐LB compared with MCI‐AD, with an AUROC of 0.67 34 and 0.85 20 (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies have measured olfactory function using standardized tests 20, 34 . Both studies found poorer olfactory function in MCI‐LB compared with MCI‐AD, with an AUROC of 0.67 34 and 0.85 20 (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Studies involving these factors would help to explore the relationship between olfactory impairment and brain amyloidbeta (Aβ) deposition and neuronal degeneration markers. Also, CSF and PET biomarkers would help in excluding mild cognitive impairment due to dementia with Lewy bodies, which is difficult to differentiate from MCI due to AD with cognitive and olfactory testing alone, according to studies 40 . No participants in the current study had evidence of Parkinsonism, prominent visual hallucinations, or rapid eye movement sleep abnormalities, as required by criteria for probable AD and MCI due to AD by NIA-AA 4,5 .…”
Section: Discussionmentioning
confidence: 99%